Discrimination of SARS-CoV-2 Omicron Sublineages BA.1 and BA.2 Using a High-Resolution Melting-Based Assay: a Pilot Study - Aoki, Akira; Adachi, Hirokazu; Mori, Yoko; Ito, Miyabi; Sato, Katsuhiko; Okuda, Kenji; Sakakibara, Toru; Okamoto, Yoshinori; Jinno, Hideto (Microbiology spectrum, 2022)
This study seeks to apply a novel high-resolution melting (HRM) assay to identify and discriminate BA.1 and BA.2 sublineages of the SARS-CoV-2 Omicron variant. Variant BA.2 may cause more severe disease than variant BA.1, meaning that identifying this variant is an important step toward improving the care of patients suffering from COVID-19. The Omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread worldwide. As of March 2022, Omicron variant BA.2 is rapidly replacing variant BA.1. As variant BA.2 may cause more severe disease than variant BA.1, variant BA.2 requires continuous monitoring. The current study aimed to develop a novel high-resolution melting (HRM) assay for variants BA.1 and BA.2 and to determine the sensitivity and specificity of our method using clinical samples. Here, we focused on the mutational spectra at three regions in the spike receptor-binding domain (RBD; R408, G446/L452, and S477/T478) for the variant-selective HRM analysis. Each variant was identified based on the mutational spectra as follows: no mutations (Alpha variant); L452R and T478K (Delta variant); G446S and S477N/T478K (Omicron variant BA.1); and R408S and S477N/T478K (Omicron variant BA.2). Upon analysis of mutation-coding RNA fragments, the melting curves of the wild-type fragments were distinct from those of the mutant fragments. The sensitivity and specificity of this method were determined as 100% and more than 97.5%, respectively, based on 128 clinical samples (40 Alpha, 40 Delta, 40 Omicron variant BA.1/BA.1.1, and 8 Omicron variant BA.2). These results suggest that this HRM-based assay is a promising screening method for monitoring the transmission of Omicron variants BA.1 and BA.2. IMPORTANCE This study seeks to apply a novel high-resolution melting (HRM) assay to identify and discriminate BA.1 and BA.2 sublineages of the SARS-CoV-2 Omicron variant. Variant BA.2 may cause more severe disease than variant BA.1, meaning that identifying this variant is an important step toward improving the care of patients suffering from COVID-19. However, screening for these variants remains difficult, as current methods mostly rely on next-generation sequencing, which is significantly costlier and more time-consuming than other methods. We believe that our study makes a significant contribution to the literature because we show that this method was 100% sensitive and over 97.5% specific in our confirmation of 128 clinical samples.